Neuroprotective Mechanisms of Ginsenoside Rb1 in Central Nervous System Diseases - Gong, Liang; Yin, Jiayi; Zhang, Yu; Huang, Ren; Lou, Yuxuan; Jiang, Haojie; Sun, Liyan; Jia, Jinjing; Zeng, Xiansi (Frontiers in Pharmacology, 2022)
Panax ginseng and Panax notoginseng, two well-known herbs with enormous medical value in Asian countries, have a long usage history in China for the therapy of some diseases, such as stroke. Ginsenoside Rb1 is one of most important active ingredients in Panax ginseng and Panax notoginseng. In the last two decades, more attention has focused on ginsenoside Rb1 as an antioxidative, anti-apoptotic and anti-inflammatory agent that can protect the nervous system. In the review, we summarize the neuroprotective roles of ginsenoside Rb1 and its potential mechanisms in central nervous system diseases (CNSDs), including neurodegenerative diseases, cerebral ischemia injury, depression and spinal cord injury. In conclusion, ginsenoside Rb1 has a potential neuroprotection due to its inhibition of oxidative stress, apoptosis, neuroinflammation and autophagy in CNSDs and may be a promising candidate agent for clinical therapy of CNSDs in the future.